Measurement of circulating cell-derived microparticles by flow cytometry: sources of variability within the assay. - Ayers, L; Kohler, M; Harrison, P; Sargent, I; Dragovic, R; Schaap, M; Nieuwland, R; Brooks, SA; Ferry, B (2011)
INTRODUCTION: Circulating cell-derived microparticles (MPs) have been implicated in several disease processes and elevated levels are found in many pathological conditions. The detection and accurate measurement of MPs, although attracting widespread interest, is hampered by a lack of standardisation. The aim of this study was to establish a reliable flow cytometric assay to measure distinct subtypes of MPs in disease and to identify any significant causes of variability in MP quantification. MATERIALS AND METHODS: Circulating MPs within plasma were identified by their phenotype (platelet, endothelial, leukocyte and annexin-V positivity (AnnV+). The influence of key variables (i.e. time between venepuncture and centrifugation, washing steps, the number of centrifugation steps, freezing/long-term storage and temperature of thawing) on MP measurement were investigated. RESULTS: Increasing time between venepuncture and centrifugation leads to increased MP levels. Washing samples results in decreased AnnV+MPs (P=0.002) and platelet-derived MPs (PMPs) (P=0.002). Double centrifugation of MPs prior to freezing decreases numbers of AnnV+MPs (P=0.0004) and PMPs (P=0.0004). A single freeze thaw cycle of samples led to an increase in AnnV+MPs (P=0.0020) and PMPs (P=0.0039). Long-term storage of MP samples at -80° resulted in decreased MP levels. CONCLUSIONS: This study found that minor protocol changes significantly affected MP levels. This is one of the first studies attempting to standardise a method for obtaining and measuring circulating MPs. Standardisation will be essential for successful development of MP technologies, allowing direct comparison of results between studies and leading to a greater understanding of MPs in disease.